Understanding barriers: patient experience with immune-mediated rheumatic diseases in Brazilian public health - Helena Tupinambá; Leticia Rocha Pereira; Carla Gottgtroy; Blanca Elena Rios Gomes Bica; Ingrid Bandeira Moss; Gabriela Sadigurschi; Ewerton Alves Portela dos Santos; Janaina Reis Xavier; Maria Cristina Caetano Kuschnir; Vitor Cardoso Doria da Gama; Thalita da Matta de Castro; Maria de Lourdes de Sousa Maia (Advances in Rheumatology, 2026)
Abstract Background Immune-mediated rheumatic diseases (IMRDs) encompass a wide range of rheumatological conditions that have a substantial impact on morbidity and mortality globally. Due to the diversified nature of IMRD symptoms, timely recognition of these conditions in primary care settings can be challenging. The duration between symptom onset and treatment initiation is a key factor influencing prognosis of IMRD. Therefore, this study aims to evaluate the medical journey of individuals with IMRD from symptom onset to treatment. Methods Cross-sectional observational study based on the analysis of questionnaire responses from 1,327 patients with IMRDs at two reference centers for rheumatic disease treatment in Rio de Janeiro. Quantitative variables were compared using the Mann-Whitney or Kruskal-Wallis test, while categorical and nominal variables were analyzed using McNemar’s test. Results The median time until the first rheumatologist consultation after symptom onset was 7 months (0,5-216 months) and the median time to obtain a definitive diagnosis of IMRD was 12 months (0,5-216 months). This period was shorter for individuals with systemic lupus erythematosus (SLE), with a median of 8 months (0.5–216 months), and longer for those with psoriatic arthritis (PsA), with a median of 33 months (2-195 months). Additionally, the median time from symptom onset to specific treatment initiation was also 12 months. It was shown that consulting two or more non-rheumatologists doctors before seeing a rheumatologist significantly delayed the IMRD diagnosis (p-value < 0.001). The diagnosis of IMRD had a negative impact on emotional well-being and occupational capacity on 85.9% ( n = 1,139) of participants’ and 68.1% ( n = 903) indicated that their work was somehow affected in a negative way. Throughout the diagnostic journey, negative feelings predominated in the period in which the diagnosis was not defined, but there was a notable shift after the confirmation of the diagnosis with an increase in positive emotions such as happiness, comfort, and well-being. Conclusions This study provides valuable information on the challenges faced in the medical journey of patients with IMRDs, from delays in diagnosis to barriers in accessing treatment and the impact on well-being, highlighting the need for multifaceted interventions to improve the management of these complex conditions.